Going somewhere : a bicycle journey across America - Benson, Brian, 1982- (New York, New York : Plume, 2014)
"Brian Benson has a million life plans but no sense of direction. So when he meets and falls for Rachel, he's ready to go wherever she'll take him. In a whirlwind of new love, they embark on a bicycle trip from northern Wisconsin to western Oregon. As the pair progress through stunning landscapes, they contend with merciless winds, vivid characters, broken bikes and bodies--and the looming question of what comes next"--
"A memoir"--Cover.
Keywords: Benson, Brian, -- 1982- -- Travel -- United States; Bicycle touring -- United States; Cycling -- Psychologocial aspects; Man-woman relationships -- Psychological aspects; Cyclists -- United States -- Biography